Many-body colloidal dynamics under stochastic resetting: Competing effects of particle interactions on the steady-state distribution - Ron Vatash; Yael Roichman (Physical Review Research)
The random arrest of the diffusion of a single particle and its return to its origin has served as the paradigmatic example of a large variety of processes undergoing stochastic resetting. While the implications and applications of stochastic resetting for a single particle are well understood, less is known about the resetting of many interacting particles. In this study, we experimentally and numerically investigate a system of six colloidal particles undergoing two types of stochastic resetting protocols: global resetting, where all particles are returned to their origin simultaneously, and local resetting, where particles are reset one at a time. Our particles interact mainly through hard-core repulsion and hydrodynamic flows. We find that the most substantial effect of interparticle interactions is observed for local resetting, specifically when particles are physically dragged to the origin. In this case, hard-core repulsion broadens the steady-state distribution, while hydrodynamic interactions significantly narrow the distribution. The combination results in a steady-state distribution that is wider compared to that of a single-particle system for both global and local resetting protocols.